Methylation profiles of IL33 and CCL26 in bronchial epithelial cells are associated with asthma. (23rd November 2018) - Larouche, Miriam; Gagné-Ouellet, Valérie; Boucher-Lafleur, Anne-Marie; Larose, Marie-Chantal; Plante, Sophie; Madore, Anne-Marie; Laviolette, Michel; Flamand, Nicolas; Chakir, Jamila; Laprise, Catherine
Aim: This study aimed to characterize DNA methylation (DNA-me) in promoter region of IL33, IL1RL1 and CCL26 in asthma and their impacts on transcriptional activity in bronchial epithelial cells (BECs).Patients & methods: We performed bis-pyrosequencing, quantitative real-time PCR and sequencing in BECs from ten asthmatic and ten control individuals.Results: We detected lower DNA-me levels of IL33 and CCL26 in asthmatic than control BECs. No correlation was found between methylation and expression levels. Interestingly, carriers of a mutative allele in a haplotype within the promoter of IL33 had a lower IL33 DNA-me level and CCL26 gene expression correlated with eosinophil count.Conclusion: These findings highlight the importance of investigating both epigenetic and genetic mechanisms in understanding the epithelial immune response in asthma.